Application of an edge detection algorithm for surface determination in industrial X‑ray computed tomography - Busch, Matthias; Hausotte, Tino (Production Engineering, 2022)
Surface determination is an essential step of the measurement process in industrial X-ray computed tomography (XCT). The starting point of the surface determination process step is a single grey value threshold within a voxel volume in conventional surface determination methods. However, this value is not always found in the reconstructed volume in the local environment of the surface of the measurement object due to various artefacts, so that none or incorrect surfaces are determined. In order to find surfaces independently of a single grey value, a three-dimensional approach of the initial contour determination based on a Prewitt edge detection algorithm is presented in this work. This method is applied to different test specimens and specimen compositions which, due to their material or material constellation, their geometric properties with regard to surfaces and interfaces as well as their calibrated size and length dimensions, embody relevant properties in the examination of joining connections. It is shown that by using the surface determination method in the measurement process, both a higher metrological structure resolution and interface structure resolution can be achieved. Surface artefacts can be reduced by the application and it is also an approach to improved surface finding for the multi-material components that are challenging for XCT.
Keywords: Metrology; Computed tomography; Surface determination; Filter application; Pre-processing; Edge detection

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (SINCE 2022: 4th Singapore International Non-Destructive Testing Conference & Exhibition, 2022)
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discusse

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes, 2022)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.<br
Keywords: Mechanical joining; Clinching; Aluminum; Characterization methods; Process-structure-property relationships

Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, Matthias; Hausotte, Tino (SHEMET 2023 (The 20th International Conference on Sheet Metal), 2021)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard. <br
Keywords: Computed Tomography; Metrology; Surface

Determination of the interface structural resolution of an industrial X-ray computed tomograph using varying gap sizes of a gauge block standard - Busch, Matthias; Hausotte, Tino (Material Science and Engineering Congress - MSE 2020, 2020)

Fiber Orientation in continuous fiber reinforced thermoplastics/metal hybrid joining via multi-pin arrays - Popp, Julian; Busch, Matthias; Hausotte, Tino; Drummer, Dietmar (Science and Engineering of Composite Materials, 2023)
Continuous fiber-reinforced thermoplastics (CFRTs) can in combination with high-strength metals offer characteristics that cannot be achieved with mono-material parts. One possible example is the combination of locally high-temperature resistance in the metal component with superior weight-related mechanical properties due to the CFRT component. This approach requires a reliable and durable joining technology, which considers the material-specific properties and allows to exploit the full potential of CFRT/metal hybrid parts. A promising approach in the field of CFRT/metal joining is the use of metallic pins, which can be embedded in the locally heated CFRT component to create a form-fitting joint. In the current state of the art, primarily single-pins are investigated and characterized: especially the distinct fiber orientation in the direct pin pressing process is only described for single-pin joints. Behind this background, the present study aims at creating an understanding of the fiber orientation mechanism for multi-pin arrays. Therefore, in the scope of this study, unidirectional reinforced glass fiber/polypropylene samples are joined via direct pin pressing and infrared heating with different 1D and 2D multi-pins arrays with different pin-diameters, spacing and pin distributions. The resulting joint morphology is consequently analyzed using micro-computer-tomography. Based on the performed investigations, a model for the fiber displacement mechanism is proposed, and the first recommendations for the design of fiber-friendly multi-pin joints with unidirectional reinforcements are given. It showed that especially pin-spacing in fiber orientation in dependency of the pin diameter is critical for a fully reconsolidated joint quality, and it is suggested that a pin-offset in the fiber direction is beneficial for a fiber-friendly joining process.<br
Keywords: hybrid joining; continuous fiber-reinforced thermoplastics; glass fiber; pin; pin joining; direct pressing; fiber orientation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (Technisches Messen, 2022)
Keywords: Messtechnik; Computertomografie; Fügetechnologie

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, Matthias; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, Tino (INTERNATIONAL DEEP-DRAWING RESEARCH GROUP CONFERENCE (IDDRG 2021), 2021)
Due to the increasing importance of reducing CO2 emissions, lightweight construction strategies are highly emphasized in the automotive industry. One of these strategies is lightweight moulding, which is used, for example, in the space frame design. Here, lightweight materials are joined with castings to form a structure that is well adapted to the application of force. Especially for multi-material joints, self-piercing riveting is frequently used as joining technology due to the wide range of joining possibilities and the high load-bearing capacities. However, the susceptibility of cast aluminium alloys to cracking due to the brittle microstructure causes great challenges for mechanical joining by self-piercing riveting. Therefore, this study investigates the suitability of the cast aluminium alloy AlSi9Mn for self-piercing riveting. Various improvement strategies are utilized to increase suitability considering of joining as well as material parameters. An evaluation of the joint and its damage characteristics is provided by metallographic analysis and industrial X-ray computed tomography (XCT). Metallographic analysis is used to determine the quality relevant characteristics of the joint, while XCT provides volumetric and non-destructive testing of the joint for internal crack
CRIS-Team WoS Importer:2021-11-05

Non-destructive testing in versatile joining processes - Lechner, Michael; Borgert, Thomas; Busch, Matthias; Harms, Arnold; Holtkamp, Pia; Kappe, Fabian; Römisch, David; Wituschek, Simon (Sheet Metal 2025, 2025)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT’s application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysi
Keywords: Computed Tomography; Metrology; Mechanical Joining

Practical Approaches for Determining the Structural Resolution Capability of X-ray Computed Tomography Measurement Tasks - Busch, Matthias; Hausotte, Tino (Metrology, 2024)
The structural resolution describes the ability of a measuring device to detect small structures on the surface of a component or test specimen by means of a quantitative value. However, the structure resolution in the computer tomograph depends on the object and must therefore be determined separately for each measurement task. Previous approaches to structure resolution determination are only related to test specimens. In this paper, less discrete approaches based on a circular pattern is presented, which can be integrated into the measured component. A voxel-based methodology as well as two surface-based methodologies are described. Investigation results regarding the effect of component position on the structural resolution are obtained on the basis of real CT measurements. A comparison is also made with the well-known hourglass method. The results show that the resolution depends on the object being measured, with similar values being obtained for the same object using different method
Keywords: Surface metrology; Structural resolution; Dimensional metrology; Siemens star; X-ray computed tomography

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2023)
In the course of the miniaturization of components, new demands are also being placed on the measuring systems intended for component inspection. In this context, the resolution of a measuring system is often of interest. As a volumetric analysis method and method of non-destructive testing, the industrial X-ray computed tomography (XCT) has the ability to measure dimensions and geometry inside a component without destroying it and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified, especially for the detectability of two surfaces facing each other. Therefore, this article describes a procedure for investigating this type of resolution with the use of a test specimen. The test specimen contains several radially arranged holes of the same size, the diameters of which also correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. The investigations are based on XCT simulations. It is shown that the detectability of the metrological surface and interface can be extended by a reasonable choice of the threshold value for surface definition within a defined interva

Simulation-based separation of mixed material joints using X-ray computed tomography - Busch, Matthias; Binder, Felix; Hausotte, Tino (ICCSE2 - 2nd International Conference on Computations for Science and Engineering, 2022)
X-ray computed tomography (XCT) is a fast-growing and non-destructive measurement technology for industrial applications. However, measuring assemblies with XCT consisting of several materials is challenging due to beam hardening or metal artifacts. The distinction between closely spaced surfaces, as in commonly used mixed materials joints like clinched connections or rivets, may even become inconclusive and limits the dimensional measurability. An improving approach to distinguish such surfaces is to use an energy-sensitive detector optimized for the specific material combination. For such an optimization a suitable spectral sensitivity has to be determined first. Therefore, a study is conducted with a simulated clinched connection probe joining two sheets of aluminum and steel and using the surface deviation error for further evaluation. The resulting spectral sensitivity curves may be used to further improve the separation of mixed material joints with dimensional XCT measurement